Dampak Karakteristik Dewan Direksi Terhadap Kinerja Perusahaan: Sektor Energi Bursa Efek Indonesia (BEI) - Suprapto, Yandi; Jolin, Jolin; Hesniati, Hesniati (Universitas Bina Sarana Informatika, 2024)
This research will examine and analyze factors such as board gender diversity, board tenure, board age, board education and managerial ownership on firm performance. The aim of this research is to determine the influence of these various factors on firm performance in the energy sector on the Indonesian Stock Exchange. The approach applied in this research uses quantitative methods by collecting secondary data. The population that is the focus of the research are several companies listed on the Indonesia Stock Exchange which operate in the energy sector. The number of samples used was 46 energy sector companies on the Indonesia Stock Exchange for the 2018-2022 period and were selected using the purposive sampling method. The data was then analyzed using multiple linear regression to determine the influence of the variables used on firm performance. The research results show that board gender diversity, board tenure, board age and board education do not have a significant influence on firm performance, however, the managerial ownership variable is proven to have a significant influence on firm performance.Keywords: Board Gender Diversity, Board Tenure, Board Age, Board Education, Managerial Ownership, Firm Performance